Effect of different types of force on the amount of tooth movement, hyaline areas, and root resorption in rats - Cuoghi, Osmar Aparecido [UNESP]; Tondelli, Pedro Marcelo; Mendonça, Marcos Rogério de [UNESP]; Aiello, Carlos Alberto; Da Costa, Silvano Cesar; Tanaka, Orlando Motohiro (Thieme, 2018)
This study evaluated the effects of using continuous, continuous interrupted, and intermittent forces on the roots and periodontal ligaments in the first molars of rats. Materials and Methods: The right first molars of 54 Wistar rats were moved with continuous force (CF group), continuous interrupted force (CIF group), or intermittent force (IF group) for 5, 7, and 9 days. Ankylosed incisors were used as anchors for the orthodontic tooth movement. To establish the different types of force, NiTi springs of 50 cN were maintained, deactivated, or removed for certain periods. Amounts of tooth movement, hyaline areas, and root resorption levels were analyzed using analysis of variance (ANOVA) and post-hoc Tukey's test with a significance level of 5%. Results: There was no difference in the amount of tooth movement between the CF and CIF groups, which differed significantly from the IF group. The CF group demonstrated a significant formation of hyaline areas, nearly 5 times more, mainly on the fifth day. Conclusions: Continuous force produced more hyaline areas with greater probability of generating root resorption. Continuous interrupted force enabled better periodontal ligament repair and more efficient elimination of hyaline areas.
Keywords: Ankylosis; Hyaline; Rats; Root resorption; Tooth movement